CADANGAN KARBON PADA POHON DI TAMAN HUTAN RAYA GUNUNG TUMPA H. V. WORANG - Wahyu D. P. A. Sardi; Reynold P. Kainde; Wawan Nurmawan (COCOS, 2022)
Abstract Taman Hutan Raya Gn. Tumpa H. V. Worang is an area that has an area of 208.81 ha with an ecological function that is able to absorb carbon because of the canopy stratification formed from a variety of vegetation, including trees, poles, saplings, seedlings where each type of plant will carry out a cycle of carbon and oxygen exchange. This study aims to analyze the total carbon storage of each tree species and the total accumulation of carbon stored in trees in the Gunung Tumpa H.V. Forest Park. people. The method used in this study is the Non-Destructive Sampling method with an observation map plot of 100 m x 100 m at the research site. The results of this study showed that there were 21 tree species with 88 individuals from 17 families where Alstonia Scholaris had the highest carbon storage value, namely 389.35 tons/ha. followed by Palaquium obavatum with a carbon storage value of 78.15 tons/ha, Dracontomelon dao 78.08 tons/ha, Lithocarpus celebicus 74.24 tons/ha, Calophyllum soulattri 35.57 tons/ha. Then the carbon value in Artocarpus atilis is 6.77 tons/ha, Dhyosphiros sp. 12.77 tons/ha, Dillenia ochereata 5.07 tons/ha, Euiginia aquea 7.28 tons/ha, Ficus benjamina 29.30 tons/ha, Ficus fistulosa 30.33 tons/ha, Gnetum gnemon 8.07 tons/ha ha, Homalium foetidum 4.80 tons/ha, Knema latericia 10.83, Laphopetalum javanicum 7.23 tons/ha, Myristyca fatua 9.67 tons/ha, Macaranga tanarius 4.63 tons/ha, Pterocarpus indicus 24.41 tons /ha, Pterospermum javanicum 10.48 tons/ha, Schleichera oleosa 8.38 tons/ha, and Terminalia copelandii 2.94 tons/ha and Accumulated total carbon storage trees in TAHURA Gn. Tumpa H.V. Worang is 838.35 tons/ha (good category). The area is about 208.81 hectares, the potential for storing carbon is 175,055.86 tons of carbon. Keywords: carbon, trees, Forest Park Gunung Tumpa H. V. worang, carbon stocks